Prática de ensino e estágio supervisionado: eixos articuladores da formação inicial dos professores da educação básica - Raymundo, Gislene Miotto Catolino (2011)
This project aimed at analyzing how the Teaching practice and supervised training are understood and experienced in the courses of initial teacher education established from the new curriculum guidelines to be applied in the basic education teachers training, specifically because of the requirements proposed by the LDB N°. 9394/96 and also by the Resolutions and Opinions of the National Education Council. The study and reflection involving these curriculum components from the new curriculum guidelines are of fundamental importance since the initial teacher training should enable the education and educational research as a unit of teaching activities, aiming at a reflexive link between the theory and practice experienced in schools and training field. In this perspective, the contribution of this paper is to discuss a proposal considered to be innovative in the process of teacher training, because it shows the disciplines of Teaching Practice and Supervised training as coordinating axes, expressing the possibility of a training that exceeds the beacons placed by traditional teaching conceptions and techniques and that enables the teacher not only to(re) define his teaching knowledge but also to understand the meaning of being a teacher. Thus, in this study, it was verified how the Pedagogy course at the Centro Universitário de Maringá has adapted the Teaching Practice and the Supervised training from the new curriculum guidelines for the teacher education curriculum and how much these components contribute to the redefinition of knowledge which are necessary to the pedagogical practice qualification, specifically for those students who are working as basic education teachers. The choice for both this institution and this course was made taking into consideration the fact that, since I am responsible for teacher training in this institution, I experience the limits and possibilities of the Teaching Practice and Supervised training which are the articulating axis of the relationship between theory and practice in the training of the future basic education teachers. To develop this research, I chose a qualitative approach, where the collection of data has been conducted through document analysis and questionnaires administered to teachers and students of the institution examined. The analysis of those documents identified how the Teaching Practice and Supervised Training are designed in a space and time which allowed for changes, learning, redefined the teaching practice and allowed to rediscover the social dimensions of being a teacher, especially for those who are already working as basic education teachers